Transition Metal Catalyzed Carbonylation Reactions Carbonylative Activation of C-X Bonds - Beller, Matthias. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Transition Metal Catalyzed Carbonylation Reactions is a comprehensive monograph focusing on carbon monoxide usage. This book provides students and researchers in organic synthesis with a detailed discussion of carbonylation from the basics through to applications. The authors have structured the book around the types of reactions, based on the different nucleophiles involved. Scientists working in carbonylation or with carbon monoxide, as well as teachers of organic synthesis can use this book to become familiar with this important area of organic chemistry.